Reliability assessment on automobile suspension system using wavelet analysis. Issue 5 (1st August 2019) - Abd Rahim, Airee Afiq; Abdullah, Shahrum; Singh Karam Singh, Salvinder; Nuawi, Mohd. Zaki
Abstract : Purpose: The purpose of this paper is to focus on the reliability assessment on the basis of automobile suspension fatigue life using wavelet decomposition method. Design/methodology/approach: The discrete wavelet transform (DWT) of automobile coil spring signal is implemented as a response to different road surfaces. A reliability analysis is applied to determine the potential of the wavelet implementation in fatigue life analysis. The signals used in this study are highway and rural road. Findings: On the basis of the implementation of wavelet decomposition method, low-level decomposition replicates the original signals in comparison with high-level decomposition. The fatigue life of low-level decomposition lies in the 2:1 and 1:2 correlation graph. The percentage difference for mean cycle to failure presents low values for low-level decomposition, with 44.31 per cent for highway and 44.20 per cent for rural road. The percentage of difference for high-level decomposition is high. Originality/value: The determination of fatigue life analysis by using the DWT method is suitable for low-level decomposition. High-level decomposition is considered noise that cannot be eliminated and does not contribute to the failure of the structure.